Developing marketing strategies for Universitas Terbuka in South Sulawesi - Abdul Rahman rahim; Hasanuddin Hasanuddin; Anfas Anfas; Syafiuddin Syafiuddin; Wahyuddin Wahyuddin (Enrichment : Journal of Management, 2023)
This research was qualitative research with a qualitative descriptive approach. It was conducted at Universitas Terbuka in South Sulawesi, with 224 samples spread across the Luwu Regency, Bone Regency, Gowa Regency, and Makassar City—data collection through questionnaires and interviews. The collected quantitative data was then processed using descriptive analysis, while the qualitative data was processed using data reduction, data display, conclusions, or verification. The results of the research conclude that: 1) The market segmentation of prospective UT students is dominated by prospective students aged 21-50, more dominated by women, most of them work in the informal sector, earn less than 5 million rupiah, and the distribution of applicants is generally in all regions level two in South Sulawesi Province; 2) The primary considerations in making a decision or making the choice to enroll at UT are the cheap tuition fees and the distance education model which allows students to study from home, study from the village, and study without having to leave their jobs, or they can work while studying; 3) The marketing strategy that must be developed includes: the marketing mix consists of 7Ps including product, price, promotion, place, people, process and physical evidence; and 4) The special characteristics that become UT's brand image include that the public considers that studying at UT is flexible: Open in the sense that UT accepts prospective new students openly without considering their biological age, diploma age, and unlimited study period and particular time. Long distance means that lectures can be carried out remotely, anytime, and anywhere, independent lectures with guidance from lecturers. Another brand image of UT is that UT can convince, serve, and meet stakeholders' satisfaction levels. Besides that, UT graduates have spread across various.